Onde estão os negros? trabalhadores da Companhia Antarctica Paulista entre 1920 e 1930 - Joaquim, Michele Silva (2023)
The present research aims to study the presence of black people in the factories of São Paulo city between 1920 and 1930, through the analysis of employee hiring records of the Companhia Antarctica Paulista during the mentioned period. Through documentary and bibliographical research, we seek to reduce the gap in historiography that demonstrates the presence of blacks in the factories of São Paulo city post-abolition. As it is a primary source research, it will contribute to studies on the diffusion of these sources, as the lack of research is largely due to lack of access to the documents. Using the Serial History methodology, which makes a social analysis through the constituted series, being it the cut and essence of the research object. A card with 15 fields of filling brought us the possibility of analyzing who these black employees of the Companhia Antarctica Paulista were: names, age, salary, housing, family and migration issues. Education, leisure and sociabilities were also addressed. The small card that was previously used to prove the existence of black people in the urban-factory environment proved to be much richer and showed us indications of this population that still lacks studies on its insertion in the city of São Paulo between 1920 and 1930